Proceedings of the 45th IEEE Conference on Decision and Control 2006
DOI: 10.1109/cdc.2006.376742
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3D Geometric Algorithm for Aircraft Autonomous Collision Avoidance

Abstract: This paper presents a novel decision-making algorithm for pair wise non-cooperative aircraft mid-air collision avoidance. An analytical solution for this control problem, based on a three dimensional geometric approach, is derived. It does not require the solution of any programming problem, thus resulting suitable for real-time applications. Moreover, the availability of an analytical solution allows the application of well assessed control analysis and synthesis techniques in order to improve stability and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 11 publications
0
59
0
Order By: Relevance
“…In [6] navigation functions are used to avoid collision between autonomous vehicles under actuation and sensing constraints, although not limited in FOV. Avoidance maneuvers for aircraft have been presented in [7] and validated for constrained sensing (both in range and in FOV), although no analytical proof of collision avoidance is presented. In [8] the authors introduce a gyroscopic force field to improve the collision avoidance capability of the navigation function for holonomic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In [6] navigation functions are used to avoid collision between autonomous vehicles under actuation and sensing constraints, although not limited in FOV. Avoidance maneuvers for aircraft have been presented in [7] and validated for constrained sensing (both in range and in FOV), although no analytical proof of collision avoidance is presented. In [8] the authors introduce a gyroscopic force field to improve the collision avoidance capability of the navigation function for holonomic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In [6] navigation functions are used to avoid collision between autonomous vehicles under actuation and sensing constraints. Avoidance maneuvers for aircraft have been presented in [7] and validated for constrained sensing (both in range and in field of view), although they leverage more geometrical reasoning than navigation functions. In [8], the authors showed that a specific navigation function, known as dipolar function, guarantees collision avoidance for agents with fixed-wing dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For collision avoidance research of UAVs or other aircrafts, Carbone et al [3] presented a novel decision-making algorithm for pair wise non-cooperative aircraft mid-air collision avoidance. And intruder is modeled as a sphere with radius R (considered as safety bubble).…”
Section: Introductionmentioning
confidence: 99%